Case 3843: Myoxus melitensis Adams, 1863 (currently Leithia melitensis; Rodentia, Gliridae): proposed precedence over Myoxus miletensis Adams, 1863 - Monaghan, Nigel T; Herridge, Victoria L; Hennekam, Jesse J (Bulletin of Zoological Nomenclature)
Noticed in BZN 78 (30 Apr 2021): 2.